2018
DOI: 10.1055/a-0630-1303
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Vitamin D Supplementation on Biomarkers of Inflammation and Oxidative Stress in Diabetic Patients: A Systematic Review and Meta-Analysis of Randomized Controlled Trials

Abstract: In this systematic review and meta-analysis of randomized controlled trials (RCTs), the effects of vitamin D supplementation on biomarkers of inflammation and oxidative stress in diabetic patients are summarized. The following databases were searched up to December 2017: MEDLINE, EMBASE, Web of Science, and Cochrane Central Register of Controlled Trials. The quality of the relevant extracted data was assessed according to the Cochrane risk of bias tool. Data were pooled using the inverse variance method and ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
29
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 53 publications
(31 citation statements)
references
References 72 publications
2
29
0
Order By: Relevance
“…Physiologically, ROS are released by inflammatory cells and the endothelium, and an exacerbated ROS production can damage cells and lead to mitochondrial dysfunction and oxidative stress in β-cells, which are related to type 1 diabetes [18,27]. For these reasons, restoring mitochondrial ROS homeostasis could be essential for preventing diabetic complications and improving endothelial function in CVDs, as demonstrated by several meta-analysis studies on antioxidant supplementation in diabetic patients [30][31][32]. Furthermore, we should remember that type 1 diabetes is an autoimmune disease; it has been shown that mitochondrial function is essential for T cell activation and function and antigen presentation (as naive and memory cells depend on efficient mitochondrial oxidative phosphorylation) [33][34][35].…”
Section: Discussionmentioning
confidence: 99%
“…Physiologically, ROS are released by inflammatory cells and the endothelium, and an exacerbated ROS production can damage cells and lead to mitochondrial dysfunction and oxidative stress in β-cells, which are related to type 1 diabetes [18,27]. For these reasons, restoring mitochondrial ROS homeostasis could be essential for preventing diabetic complications and improving endothelial function in CVDs, as demonstrated by several meta-analysis studies on antioxidant supplementation in diabetic patients [30][31][32]. Furthermore, we should remember that type 1 diabetes is an autoimmune disease; it has been shown that mitochondrial function is essential for T cell activation and function and antigen presentation (as naive and memory cells depend on efficient mitochondrial oxidative phosphorylation) [33][34][35].…”
Section: Discussionmentioning
confidence: 99%
“…Human ex vivo studies indicate that vitamin D exerts anti-inflammatory effects on uremic lymphocytes under renal replacement therapy (RRT) [96]. Meta-analyses demonstrating reduced circulating markers of inflammation in mostly non-CKD subjects on vitamin D supplementation [97,98], further supporting a significant role of vitamin D on the hallmarks of ageing. However, these associations were not seen in CKD patients on vitamin D supplementation [99].…”
Section: The Endocrine Phosphate-fgf-23-klotho Axis and Premature Agementioning
confidence: 99%
“…The contribution of oxidative stress to the cardiovascular complications in diabetes is widely accepted [102,103]. A meta-analysis of 33 studies revealed that administration of vitamin D significantly reduced the serum levels of high-sensitivity C-reactive protein (hs-CRP) and MDA levels in diabetic patients, whereas vitamin D treatment increased • NO bioavailability and the levels of reduced glutathione [104]. Although vitamin D is not a classical low-molecular-weight antioxidant compound, its beneficial effects on oxidative stress are more and more recognized [105][106][107][108].…”
Section: Clinical Evidence For a Role Of Oxidative Stress In Cardiovamentioning
confidence: 99%